2009
DOI: 10.1063/1.3155196
|View full text |Cite
|
Sign up to set email alerts
|

10-nm-thick quinary (AlCrTaTiZr)N film as effective diffusion barrier for Cu interconnects at 900 °C

Abstract: In this study, an ultrathin quinary nitride film (AlCrTaTiZr)N of only 10 nm thick has been developed as a diffusion barrier layer for Cu interconnects. The (AlCrTaTiZr)N nanocomposite film was constructed of nanocrystallites embedded in an amorphous matrix. At an extremely high temperature of 900 °C, the Si/(AlCrTaTiZr)N/Cu film stack remained thermally stable. Neither interdiffusion between Si and Cu through the (AlCrTaTiZr)N layer nor formation of any silicides occurred. The nanocomposite structure and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…As long as the change in structure due to annealing is insignificant (700-900 °C), the strengthening effect is still retained. In addition, the excellent capability of high-entropy nitrides to retain the original structure at high temperatures is also reported by Huang, Lai, and Chang [26,34,35]. Annealing at 1000 °C decreases the film hardness value to 26 GPa, but this value is still higher than that of commercial TiN coatings [36].…”
Section: Thermal Stability and Film Hardnessmentioning
confidence: 76%
“…As long as the change in structure due to annealing is insignificant (700-900 °C), the strengthening effect is still retained. In addition, the excellent capability of high-entropy nitrides to retain the original structure at high temperatures is also reported by Huang, Lai, and Chang [26,34,35]. Annealing at 1000 °C decreases the film hardness value to 26 GPa, but this value is still higher than that of commercial TiN coatings [36].…”
Section: Thermal Stability and Film Hardnessmentioning
confidence: 76%
“…In a pure element or dilute solid solution, the potential energy associated with each lattice site is approximately equal, whereas in an HEA there will be sites in which the bonding configuration will be more preferable for a diffusing species than others, and these act as temporary traps, slowing the rate of diffusion. Others have suggested that lattice distortions are also associated with slow diffusion in HEAs, 69,181 and it seems reasonable to expect fluctuations in the potential energies of sites in a distorted lattice.…”
Section: Sluggish Diffusion Kineticsmentioning
confidence: 99%
“…[4][5][6]8,209 This has been used to explain particular experimental observations in a number of studies. 1,52,53,55,65,69,75,100,124,166,181,205,[210][211][212][213][214] Yeh et al 5,6,8,209 have suggested that anomalously slow diffusion in HEAs originates from fluctuations in the potential energies of lattice sites that are met by diffusing species, Fig. 6.…”
Section: Sluggish Diffusion Kineticsmentioning
confidence: 99%
See 2 more Smart Citations